INVESTIGAÇÃO DA SEQUÊNCIA SÍSMICA INICIADA PELO SISMO DE ARRAIOLOS (15/1/2018, ML=4.9) - Matias, Luis (2019)
The Arraiolos earthquake occurred the 15th January 2018 at 11:51 UTC with a magnitude ML=4.9 The main shock was followed by many aftershocks, some of them felt by the population, such as the ML=3.1 2018-02-01 event. A few hours after the main shock the ICT (Instituto de Ciências da Terra, Évora) and the IDL (Instituto Dom Luiz) began the deployment of a dense temporary seismic network that attained a total of 35 seismic station, some short period and others broadband. We present in this work the preliminary results obtained with the temporary seismic network complemented with the IPMA permanent stations. Until the 25th February we analysed 294 earthquakes with 6 or more phase readings and a GAP less than 180o. We present the epicentre and hypocentre maps, the time and magnitude distributions, the focal mechanisms and sequences identified by waveform similarity. We also computed the static stress transfer caused by the main shock and its influence on the seismic sequence.